Literary Trials Exceptio Artis and Theories of Literature in Court - Grüttemeier, Ralf (Bloomsbury Academic, 2016)
From the 19th century onwards, famous literary trials have caught the attention of readers, academics and the public at large. Indeed it is striking that more often than not, it was the texts of renowned writers that were dealt with by the courts, as for example Gustave Flaubert's Madame Bovary and Charles Baudelaire's Les Fleurs du Mal in France, James Joyce's Ulysses and Henry Miller's Tropic of Cancer in the US, D.H. Lawrence's Lady Chatterley's Lover in Great-Britain, up to the more recent trials on Klaus Mann's Mephisto and Maxim Biller's novel Esra in Germany. By bringing together international leading experts, Literary Trials represents the first step towards a systematic discussion of literary trials on a global scale. Beginning by first reassessing some of the most famous of these trials, it also analyses less well-known but significant literary trials. Special attention is paid to recent developments in the relationship between literature and judicature, pointing towards an increasing role for libel and defamation in the societal demarcation of what literature is, and is not, allowed to do. This title was made Open Access by libraries from around the world through Knowledge Unlatched.